Fatigue behaviour of maraging steel samples produced by SLM under constant and variable amplitude loading - Branco, R. (2019)
This paper addresses the fatigue behaviour of AISI 18Ni300 samples manufactured by selective laser melting under both constant- and variable-amplitude loading. The fatigue campaign encompasses a series of low-cycle strain-controlled fatigue tests performed under fully-reversed conditions at various strain amplitudes, and a series of high-cycle stress-controlled fatigue tests performed under pulsating conditions at various stress ranges considering both constant- and variable-amplitude loading spectra. Fatigue life predictions are performed on the basis of the SWT parameter along with the Miner’s law. This approach has demonstrated to be sufficiently reliable to predict the lifetime expectancy in maraging steel samples produced by selective laser melting